Thinking Through the Tiger: Korean Cultural Identity, Space, and Time - Eunkyung Yi (Humanities)
In the region of Northeast Asia, Korea has been identified as a nation that has a distinctive affinity for tigers. Koreans’ lives are deeply ingrained with emotions and thoughts related to tigers, even though they have completely disappeared from Korea due to historical changes and urbanization. This study first connects the image of tigers in Korean creation myths and folk tales with cultural identity. The analysis uncovers that the satire and humor present in the literature and paintings depicting tigers were employed to surmount the realistic fears associated with these creatures. Subsequently, the study delves into historical perceptions and spatial concepts by examining folk tales and maps of the Korean Peninsula that are symbolized by tigers. During the Japanese colonial period, tigers were regarded as a symbol of Korean national consciousness, and since then, they have played a significant role in disseminating national spirit and identity discourse. Finally, the analysis of Korean proverbs related to tigers reveals the profound influence of these animals on the development of Korean concepts of seasons and time. This study thus demonstrates the significant role of tigers in shaping the cultural identity and conceptual framework of space and time in Korea.